Reactive airways dysfunction syndrome caused by bromochlorodifluoromethane from fire extinguishers. Issue 8 (16th July 2004) - Matrat, M; Laurence, M F; Iwatsubo, Y; Hubert, C; Joly, N; Legrand-Cattan, K; L'Huillier, J P; Villemain, C; Pairon, J C
Abstract : Although the neurological and cardiovascular effects of Freons have been extensively described, the respiratory effects have been less well documented. We report four cases of occupational asthma following accidental exposure to bromochlorodifluoromethane (Halon 1211) due to release of the contents of a fire extinguisher. All subjects developed an irritative reaction of the upper airways and lower respiratory symptoms immediately after exposure. Non-specific bronchial hyperreactivity was present for at least two months in all subjects and was still present more than two years after exposure in one case. The diagnosis of reactive airways dysfunction syndrome can be adopted in at least three of these four cases.